The GALAH survey: verifying abundance trends in the open cluster M67 using non-LTE modelling - Gao, Xudong; Lind, Karin (Monthly notices of the Royal Astronomical Society, 2018)
ABSTRACT. Open cluster members are coeval and share the same initial bulk chemical composition. Consequently, differences in surface abundances between members
Gesehen am 16.12.2019